Telaah Penafsiran Ayat-Ayat Kekerasan: Upaya Mewujudkan Perdamaian dalam Bingkai Keindonesiaan - Lufaefi Lufaefi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2017)
Issues of violence and radicalism in Indonesia increasingly prevalent. Various acts of anarchism and terrorism seem to be mushrooming in this country that has a lot of diversity. Actions that harm the public and even the religion is not rare background against the understanding of the holy verses of the Koran. The Qur’an is understood as a revelation that legalizes these actions. Then, is it true that the revelation of the Qur’an permits acts of violence that would harm many people? this article attempts to interpret the verses of the Koran that are justified as supporting verses of the above mentioned actions. Through the historical review of the verse (asbab an-nuzul), in fact none of the Qur’anic verses permit violence, terrorism and radicalism. As a revelation coming from the Lord of the universe, indeed the verses of the Koran precisely require creating peace for the whole of nature, not least the nature of Indonesia.